PJMHS 2021
DOI: 10.53350/pjmhs211571745
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Practice of Fresh Dental Graduates, Dental Surgeons and Specialists of Multan about Different LA Techniques for Mandibular Teeth: A cross-sectional survey

Abstract: Objective: To assess the knowledge about different mandibular nerve block techniques of fresh dental graduates, dental surgeons and specialists to attain mandibular nerve block for dental treatment in Multan. Design of the Study: It was a cross-sectional survey. Study Settings: This study was carried out at Department of Dentistry at Multan Medical & Dental College, Nishtar Institute of dentistry (Nishtar Medical University) and Bakhtawer Amin Dental College from August 2019 to August 2020. Material and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…On the other hand, they expressed the least confidence in performing the sphenopalatine nerve block (5.2%), the Vazirani-Akinosi technique (7.5%), and Gow-Gates mandibular block (11.3%). According to the study from Pakistan conducted on dentists with and without specialization, 51.3% of the respondents reported that they knew the technique for applying the Gow-Gates mandibular block, but their self-assessment of competence in successfully performing this technique was only 5.14 on a scale of 0 to 10 [45]. Based on the provided information, it can be inferred that dentists exhibit higher confidence levels and a greater frequency of usage when employing the lower alveolar block technique compared to the Gow-Gates mandibular block technique.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they expressed the least confidence in performing the sphenopalatine nerve block (5.2%), the Vazirani-Akinosi technique (7.5%), and Gow-Gates mandibular block (11.3%). According to the study from Pakistan conducted on dentists with and without specialization, 51.3% of the respondents reported that they knew the technique for applying the Gow-Gates mandibular block, but their self-assessment of competence in successfully performing this technique was only 5.14 on a scale of 0 to 10 [45]. Based on the provided information, it can be inferred that dentists exhibit higher confidence levels and a greater frequency of usage when employing the lower alveolar block technique compared to the Gow-Gates mandibular block technique.…”
Section: Discussionmentioning
confidence: 99%